Hierarchical Hollow Co/N-C@NiCo2O4 Microsphere as an Efficient Bi-functional Electrocatalyst for Rechargeable Zn–Air Battery - Song, Yuke; Xie, Wenfu; Li, Shijin; Guo, Jian; Shao, Mingfei (Frontiers in Materials, 2019)
Zn–air batteries (ZABs) are one of the promising power sources for portable and wearable electronic devices because of their high theoretical specific energy density and low cost. However, their practical performance with high energy density and power density is difficult to maintain under high mass-loading due to the compact restacking that seriously hinders mass/charge diffusion. Herein, we reported an efficient bi-functional electrocatalyst of Ni-Co mixed metal oxides incorporated cobalt/nitrogen doped carbon with hierarchical hollow nanostructure (H-Co/N-C@NiCo2O4). Benefiting from this structural and compositional merits, the as-synthesized H-Co/N-C@NiCo2O4 exhibits excellent electrocatalytic activity and long-term stability for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The potential gap between half-wave potential in ORR and overpotential at a current density of 10 mA cm−2 in OER reaches within 0.8 V, much smaller than that of most reported bi-functional electrocatalysts. Moreover, H-Co/N-C@NiCo2O4 is constructed as an air electrode for rechargeable ZAB, delivering a high power density and long cycling stability. A good linear relationship has been achieved between the power density and various mass-loading of H-Co/N-C@NiCo2O4 on the electrode, indicating well preserved performance even under high dense packing of catalysts, which provides a promising paradigm for the practical applications in ZAB.